2017
DOI: 10.1080/03019233.2017.1368958
|View full text |Cite
|
Sign up to set email alerts
|

Formation and evolution of macro inclusions in IF steels during continuous casting

Abstract: The evolution of macro inclusions during continuous casting was investigated by large-area inclusion characterization using ASPEX and analysis of nozzle blockage deposits. Six kinds of inclusions over 5 μm were observed in samples taken from the tundish and the slabs: single alumina particles, alumina dendrites, refractory-related alumina, alumina associated with bubbles, alumina clusters and Al-Ti complex oxides. By examining the morphology of the nozzle blockage deposit, it was concluded that the refractory-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
26
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 30 publications
0
26
0
Order By: Relevance
“…Cui et al and Rödl et al found Ti‐rich phases, either FeO.TiO 2 or Al 2 O 3 .TiO 2 , acting as binder phase between alumina inclusions. Other investigations revealed the presence of different layers, from coarse alumina clusters near the liquid steel to Al 2 O 3 –TiO 2 ‐layers at the steel refractory interface . Additionally alumina inclusions with low contents of TiO x were found by several authors .…”
Section: Introductionmentioning
confidence: 90%
See 1 more Smart Citation
“…Cui et al and Rödl et al found Ti‐rich phases, either FeO.TiO 2 or Al 2 O 3 .TiO 2 , acting as binder phase between alumina inclusions. Other investigations revealed the presence of different layers, from coarse alumina clusters near the liquid steel to Al 2 O 3 –TiO 2 ‐layers at the steel refractory interface . Additionally alumina inclusions with low contents of TiO x were found by several authors .…”
Section: Introductionmentioning
confidence: 90%
“…In most cases the occurrence of Ti‐bearing phases and inclusions is also accompanied by certain amounts of entrapped and solidified steel within the clogging structure, caused by the increased wettability of Al 2 O 3 –TiO x inclusions. A widespread theory believes in local reoxidation in the casting system as the origin of these particles …”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4]. Hence, the removal of inclusions from the molten steel is a critical issue throughout the steelmaking process.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, large inclusions would also be formed during casting process. The composition evolution, growth, and collision of non‐metallic inclusions during casting process have also attracted more and more attention . Choi et al investigated the evolution of oxide inclusions during solidification in 304 stainless steel slab .…”
Section: Introductionmentioning
confidence: 99%
“…They concluded that a combination of pre‐existing inclusions and inclusions precipitated during solidification caused composition change. Deng et al investigated formation and evolution of macro‐inclusions in IF steels during continuous casting and found that mass fraction of Al 2 O 3 in inclusions increased in steel slab . Nurmi et al reported that new inclusions formed during solidification in high‐carbon Si/Mn‐deoxidized steel .…”
Section: Introductionmentioning
confidence: 99%